TI_GERICHTE 12.2007.33 vom 9. Juli 2007 , contratto di lavoro, pagamento di giorni di riposo non goduti e della tredicesima - TI Tribunale d'appello (2007)
contratto di lavoro, pagamento di giorni di riposo non goduti e della tredicesima